Synthesis and biological evaluation of a library of glycoporphyrin compounds. - SCANLAN, EOIN; SENGE, MATHIAS (My University, 2012)
A library of glycosylated porphyrins (Glycoporphyrins) was prepared and evaluated for their PDT activity against oesophageal squamous cell carcinoma cell line OE21 in vitro. Synthetic methodology was developed to allow incorporation of biologically active carbohydrates including the histo blood group antigen trisaccharide, Lewis x onto the porphyrin backbone. The effect of the carbohydrate group and substitution pattern on the PDT activity, cell uptake and subcellular localisation of the glycoporphyrin compounds is reported.
PUBLISHED
PubMed ID: 23018896
Keywords: Cancer